(untitled) (Journal of the College of Basic Education, 2023)
The Chinese cultural and intellectual expansion, during the imperial era, left great traces inAll of the Far East and Southeast Asia. And he had a role in subjugating most of these countries.The region is under the sovereignty of the Chinese Empire, recognizing that it is a superpower that is superior to it civilized.And think. This was evident in the subordination of the Kingdom of Liuchi (1) to the Empire of the Middle (China).One of the manifestations of this was its annual payment of tribute to China, but without the latter’s interference in the matter.its internal affairs. The Liuchiu Kingdom maintained that status for a long time.But after the opening of the Far East region, especially China and Japan, to the outside world,in the mid-nineteenth century, and their exposure to international influences, and the varying responses of eachFor those influences, China’s repeated defeat, and Japan’s revival from its slump, after all of that, isDid the Kingdom of Liuchiu maintain its dependence on the Chinese Empire? How did it affect the renaissance?Modern Japan on that? Has the Chinese government maintained its sovereignty over it?